2021
DOI: 10.1177/11297298211039653
|View full text |Cite
|
Sign up to set email alerts
|

Needle-free connectors to prevent central venous catheter occlusion at a tertiary cardiac center: A prospective before and after intervention study

Abstract: Objectives: To evaluate the effectiveness of needle-free connectors to maintain Central Venous Catheter—CVC patency. Background: Loss of patency is a common complication associated with CVC. For patients, this can be stressful and painful, and can result in a delay in infusion therapy. Pressure-activated anti-reflux needle-free connectors are one of the most modern devices; however, no studies have compared this connector with the open-system three-way stopcock in terms of the incidence of CVC occlusion. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Studies measuring the clinical performance of NCs with the functional anti-reflux diaphragm design are limited. One study demonstrated increased patency of catheters using pressure activated anti-reflux NCs in comparison to stopcock devices [32]. There are no known studies evaluating the performance of an NC with anti-reflux technology compared to its exact design counterpart without anti-reflux technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies measuring the clinical performance of NCs with the functional anti-reflux diaphragm design are limited. One study demonstrated increased patency of catheters using pressure activated anti-reflux NCs in comparison to stopcock devices [32]. There are no known studies evaluating the performance of an NC with anti-reflux technology compared to its exact design counterpart without anti-reflux technology.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have demonstrated that NCs without bi-directional flow control are associated with unintended complications, such as intraluminal thrombotic catheter occlusions and central line associated bloodstream infections (CLABSI) that negatively impact patient safety [28][29][30][31]. Furthermore, an experimental study revealed a correlation between blood reflux volume and intraluminal thrombotic catheter occlusion rates [32]. Based on this study, it is reasonable to hypothesize anti-reflux technology may optimize catheter function and reduce consequences associated with blood reflux including delayed treatment [33], device replacement [34], infection [16][17][18], and increased cost [28,29,33,34].…”
Section: Type Of Nc Descriptionmentioning
confidence: 99%